DETERMINAN KEPUTUSAN GENERASI Z DALAM MELAKUKAN PEMBAYARAN ZIS MELALUI DIGITAL PLATFORM - Nurul Aini; Paksi, Girindra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to analyze the influence of perceived ease of use, perceived usefulness, zakah literacy, and income on generation z's decision to make digital payments for Zakah, Infaq, and Sedekah (ZIS). The research method employed in this study is quantitative primary data with 412 respondents representing generation z in Indonesia. The model used in this research employs logistic regression analysis for data processing and analysis. The results indicate that only two factors play a significant role: perceived ease of use and zakah literacy as determinants influencing generation z's decision toward digital ZIS payment services in Indonesia. This research underscores the importance of perceived usefulness, perceived ease of use, zakah literacy, and income in influencing generation z's decisions regarding digital ZIS payments. The findings of this study are expected to enhance institutions' strategies for optimizing ZIS collection and improving generation z's perception of digital ZIS payments.